Effect of Crude Extract of Saponin of Seeds Sesbania Sesbon on Cholesterol Level in Blood of Mice - Athraa Hussein Ali (Journal of Madenat Alelem University College, 2014)
The current Study was carried out to determine the effect of different concentrations (0.03, 0.06, 0.12, 0.25) of crude extract of saponin seeds Sesbania sesbon (L) Merrill on the haemolytic activity of saponin on red blood corpuscles under laboratory conditions. Results indicated that percentage of haemolysis was 100% at concentrations 0.12 and 0.25 of saponin but the activity of saponin blocked by adding different concentrations (0.2, 0.4, 0.6, 0.8, 1) % of cholesterol. Thus, negative relationship was found between haemolytic activity of saponin and cholesterol concentration. No observable lysis was found at 1% of cholesterol. The effect of sesban saponin extract on the cholesterol level of mice blood at different time intervals (4, 8, 12 hours) post injection showed decrease in cholesterol level when increased saponin concentration with decreasing the period of injection. The lowest level of cholesterol observed in mice that injected with 0.12 and 0.25 of saponin after 4 and 8 hour of injection.